Concentrations of atomoxetine and its metabolites in plasma and oral fluid from paediatric patients with attention deficit/hyperactivity disorder. Issue 6 (16th May 2012) - Papaseit, Esther; Marchei, Emilia; Farré, Magí; Garcia‐Algar, Oscar; Pacifici, Roberta; Pichini, Simona
<x xml:space="preserve">Abstract</x> Atomoxetine (ATX) is a non‐stimulant drug approved for the treatment of children and adolescents with attention deficit/hyperactivity disorder (ADHD). We aimed to study the excretion profile of ATX and its principal metabolites 4‐hydroxyatomoxetine (4‐OH‐ATX) and N‐desmethylatomoxetine (desmethyl‐ATX) in oral fluid and plasma of ADHD paediatric subjects, after administration of different dosage regimens. Oral fluid and plasma samples were obtained from one child and five adolescents treated with different ATX doses (18–60 mg/day). ATX and its metabolites were measured in oral fluid and plasma by liquid chromatography‐mass spectrometry (LC‐MS). Apparent pharmacokinetic parameters of ATX in oral fluid and plasma were estimated for each subject. All analytes under investigation were detected in plasma samples with concentrations from 0.6 to 1065.7 ng/ml for ATX, 0.7 to 17.1 ng/ml for 4‐OH‐ATX and 0.7 to 126.2 ng/ml for desmethyl‐ATX. Only ATX and 4‐OH‐ATX were detected in oral fluid samples with concentrations from 0.5 to 36.0 ng/ml and 0.5 to 4.7 ng/ml, respectively. ATX concentrations in oral fluid were between one and two orders of magnitude lower than those in plasma. 4‐OH‐ATX was found in oral fluid at a peak concentration approximately one‐fourth those in plasma with a mean tmax of 2.3 in plasma and 3.0 h in oral fluid. The correlations between ATX and 4‐OH‐ATX concentrations in the two biological fluids indicate that oral fluid concentrations of this drug and its principal metabolite may be a predictor of plasma concentrations, even if values are too low and variable to be considered an alternative to plasma. Copyright © 2012 John Wiley & Sons, Ltd.